Phase transitions and phase separation in a pseudospin-electron model with direct interaction between pseudospins and with transverse ﬁeld - Dublenych, Yu.I. (Condensed Matter Physics, 2000)
The pseudospin-electron model with a direct interaction between pseudospins and with transverse ﬁeld is considered. In the absence of electron
transfer, the equilibrium states of the model are studied in the mean ﬁeld
approximation. In the µ = const regime, two types of the ﬁrst order phase
transitions (with jumps of the mean values of pseudospins and average
electron concentration) are revealed. At T → 0 , phase transitions of the
ﬁrst type disappear, on increasing the transverse ﬁeld, while those of the
second type persist at any large value of the ﬁeld. The phase transitions of
the second type are caused by simultaneous effect of pseudospin-electron
interaction and transverse ﬁeld. It is also shown that in the n = const
regime at zero temperature, the phase separation occurs at all values of a
longitudinal ﬁeld h . В наближенні середнього поля досліджено рівноважні стани псевдоспін-електронної моделі з прямою взаємодією псевдоспінів та з поперечним полем за відсутности перенесення електронів. У режимі
µ = const виявлено фазові переходи першого роду (зі стрибкоподібною зміною середнього значення псевдоспіна та середньої електронної концентрації) двох типів: перші у випадку T → 0 зникають зі
збільшенням поперечного поля, інші залишаються, яким би великим
не було це поле. Фазові переходи другого типу зумовлені одночасним впливом псевдоспін-електронної взаємодії та поперечного поля. Показано також, що в режимі n = const за нульової температури
відбувається розшарування фаз в усій області значень поздовжнього
поля h .